Copper-iron alloy material and preparation method thereof

Through induction smelting and jet deposition processes, combined with the use of nano powders and trace elements, the problems of complex and cost of existing copper-ferroalloy materials are solved, and the industrial production of copper-ferroalloy materials with high strength, high conductivity and good electromagnetic shielding effect are achieved.

CN119640087APending Publication Date: 2025-03-18INNER MONGOLIA METAL MATERIAL RES INST +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411515206.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing copper-ferroalloy materials are made of complex methods and high equipment requirements, which are not suitable for large-scale production, resulting in increased production costs.

Method used

Induction smelting combined with jet deposition technology, nano Cu powder and nano WC powder are prepared in a specific proportion and pressed into a block, and trace amounts of Mg and Nb are added, and multiple passages of precision forging and annealing are carried out to prepare copper-ferroalloy materials with high strength, high conductivity and good electromagnetic shielding effect.

Benefits of technology

It realizes the high strength, high conductivity and good electromagnetic shielding effect of copper-ferroalloy materials, while simplifying the process flow, improving production efficiency, reducing production costs, and being suitable for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a copper-iron alloy material and a preparation method thereof, and the copper-iron alloy material comprises the following components in percentage by weight: 9-17% of Fe, 0.05-0.1% of Nb, 0.1-0.2% of WC, 0.02-0.04% of Mg, and the balance of Cu and inevitable impurities. The preparation method comprises the following steps: induction melting; performing hot forging treatment; performing peeling treatment; cold forging treatment; annealing treatment; pickling treatment; and cold forging treatment. The trace Mg element plays a role in further deoxidation, and the situation that the mechanical and electrical properties are reduced due to the fact that the oxygen content of the alloy material is too high is avoided; the trace Nb serves as the core of heterogeneous nucleation, grain refinement is facilitated, and the low-content Nb basically does not affect the conductivity of the alloy; and the trace WC particles can further strengthen the matrix and improve the high-temperature softening resistance of the alloy. In addition, the problem of segregation of Fe and WC is solved by adopting a spray deposition process, and the method is simple in process, high in production efficiency and easy to apply to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a copper-iron alloy material and a preparation method thereof. Background Art

[0002] Copper-iron alloys are widely used in connectors, 5G heat sinks, electronics, shielding covers and other fields due to their excellent mechanical, electrical, thermal conductivity, ductility and good electromagnetic shielding properties. However, due to the inherent properties of copper and iron themselves, the effective preparation of copper-iron alloys in the current manufacturing field is still very difficult. This is mainly due to the large difference in the specific gravity of iron and copper. When the mass fraction of iron is lower than 2.5%, iron mainly exists in the copper matrix in the form of solid solution; when the mass fraction of iron is higher than 5%, segregation behavior will occur, requiring special metallurgical control measures.

[0003] At present, the methods for preparing copper-iron alloy materials at home and abroad mainly include: mechanical alloying method, gas atomization method, deformation in-situ composite method, external field electromagnetic stirring melting method, etc.

[0004] For example, the Chinese invention patent "A method for preparing a Cu-Fe composite material" with application number CN201410493879.8 (authorization announcement number CN104232962B) has a composition (mass percentage) of Fe: 12-48%, Cu: 52-88%, and a preparation method of the Cu-Fe composite material: Cu powder and Fe powder are mixed by ball milling and then sieved, and then pre-pressed, hot-pressed and sintered at high temperature, solution treated, and aged in sequence to obtain a Cu-Fe composite material, and the hardness of the Cu-Fe composite material is ≥120HB and the tensile strength is ≥500MPa.

[0005] For example, the Chinese invention patent with application number CN202010646093.0 "A high-conductivity and high-strength copper-iron-calcium alloy and its preparation method" (authorization announcement number CN111593227B), its components (mass percentage) are Fe: 0.05~35%, Ca: 0.01~2%, and the remainder is Cu and inevitable impurities. Its preparation method is: the copper-iron-calcium alloy raw material is prepared into alloy powder by atomization method, and then the alloy powder is sintered, and then cold processed and aged to obtain a high-conductivity and high-strength copper-iron-calcium alloy. The copper-iron-calcium alloy obtained by this invention patent has a tensile strength of ≥550MPa, a conductivity of ≥75%IACS, and an elongation at break of ≥25%.

[0006] For example, the Chinese invention patent application with application number CN202010266513.2, "A microalloying method for improving the comprehensive mechanical properties of Cu-Fe alloys" (application publication number CN111334683A), has the following components (mass percentage): Fe: 0.5-4%, Sn: 0.05-0.5%, and the remainder is Cu and unavoidable impurities. Its preparation method is: copper-iron alloy ingots are prepared by vacuum induction melting combined with electromagnetic stirring technology. The copper-iron alloy obtained in this application has a tensile strength of 294.8 MPa, a yield strength of 122.5 MPa, and an elongation of 42.4%.

[0007] For example, the Chinese invention patent with application number CN202111193832.6, "A Cu-Fe-Re in-situ composite strengthened copper alloy material and its preparation method" (authorization announcement number CN113913643B), has the following components (mass percentage): Fe: 5-16%, Re: 0.02-0.12%, and the remainder is Cu and unavoidable impurities. Re is a mixture of La and Ce. Its preparation method is: smelting, electromagnetic continuous casting, hot extrusion, cold drawing, primary annealing, cold drawing, intermediate annealing, cold drawing, and finished product annealing. The in-situ composite strengthened copper-iron alloy material obtained by the invention has a tensile strength of ≥700MPa, an elongation after fracture of ≥7%, a Vickers hardness of ≥190HV, an electrical conductivity of ≥60%IACS, and an electromagnetic shielding performance of ≥80dB at 100KHz to 10GHz.

[0008] For example, the Chinese invention patent with application number CN202010406862.X "A high-conductivity and high-strength copper-iron alloy and its preparation method" (authorization announcement number CN111424188B), its composition (mass percentage) is Fe: 5~25%, the balance is Cu and inevitable impurities, and its preparation method is: atomization method is used to prepare alloy powder, pressure sintering, atmosphere sintering, cold working, aging, cold working, aging, cold working, aging to prepare copper-iron alloy. The tensile strength of the copper-iron alloy obtained by this invention patent is 620~1060Mpa, and the conductivity is 50~70%IACS.

[0009] With the rapid development of science and technology, components are gradually in a complex and changeable working environment, which also puts forward higher requirements on the high temperature stability of copper-iron alloys. The above copper-iron alloy preparation method can obtain copper-iron alloys with good quality and performance, but the preparation process is generally more complicated, with high requirements on equipment, which is not suitable for large-scale production, resulting in a significant increase in production costs. Therefore, it is necessary to develop a copper-iron alloy material preparation method with simple process, high production efficiency and great industrial production potential. Summary of the invention

[0010] The first technical problem to be solved by the present invention is to provide a copper-iron alloy material with high strength, high conductivity, good electromagnetic shielding effect and good resistance to high temperature softening performance in view of the current status of the prior art.

[0011] The second technical problem to be solved by the present invention is to provide a method for preparing the copper-iron alloy material with simple process, high production efficiency and great industrial production potential.

[0012] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a copper-iron alloy material, characterized in that it is composed of the following components in weight percentage: Fe: 9-17%, Nb: 0.05-0.1%, WC: 0.1-0.2%, Mg: 0.02-0.04%, and the balance is Cu and inevitable impurities.

[0013] Preferably, the copper-iron alloy material has a tensile strength of 642-837 MPa, a conductivity of 52.3-68.6% IACS, an elongation after fracture of 4%-8.5%, a softening temperature of ≥600° C., and an electromagnetic shielding effect of ≥87 dB.

[0014] The technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing the copper-iron alloy material as described above, characterized in that the steps are as follows:

[0015] 1) Induction melting: Nano Cu powder and nano WC powder are prepared in a mass ratio of (4-8):1 and mixed evenly, and then pressed into WC-Cu blocks by a cold isostatic press; the prepared raw materials: high-purity copper, pure Fe blocks, and pure Nb blocks are placed in an induction furnace and induction melted under the protection of N2 atmosphere, and a molten liquid is obtained after the raw materials are completely melted, and then a trace amount of Mg and WC-Cu blocks are added to the molten liquid and kept at a temperature of 1310-1420°C for 3-5 minutes, and then the induction melting power is reduced to 18-20KW for spray deposition molding to obtain an ingot;

[0016] 2) Hot forging treatment: placing the billet obtained in step 1) in a holding furnace for homogenization treatment, then taking out the billet for multiple passes of fine forging treatment to obtain an alloy rod, thereby improving the casting defects of the deposited billet;

[0017] 3) Peeling treatment: Descaling the surface of the alloy rod obtained in step 2) to improve the surface quality of the alloy rod;

[0018] 4) Cold forging treatment: The alloy rod peeled in step 3) is subjected to multiple passes of fine forging treatment at room temperature to break up the grains and the coarse second phase;

[0019] 5) Annealing: Annealing the alloy rod after cold forging in step 4) to improve the electrical conductivity and ductility of the alloy;

[0020] 6) Pickling treatment: Pickling the alloy rod after annealing in step 5) to remove the oxide scale on the surface of the alloy rod after annealing;

[0021] 7) Cold forging treatment: The alloy rod after the pickling treatment in step (6) is subjected to multiple passes of fine forging treatment at room temperature to improve the mechanical properties of the alloy and obtain a copper-iron alloy material.

[0022] In the above step 1), a small amount of nano WC powder and nano Cu powder are mixed uniformly in a mass ratio of 1: (4-8) and pressed into a block, which, combined with the spray deposition process, can further solve the problem of element segregation.

[0023] Preferably, the process of spray deposition in step 1) is: the atomization pressure is 0.9-1.1 MPa, the scanning frequency is 23-28 Hz, the deposition disk rotation frequency is 3.0-3.5 Hz, and the melt is deposited into an ingot with a diameter of 78-85 mm and a height of 390-420 mm.

[0024] Preferably, in step 1), after the raw materials are completely melted, the temperature is kept at 1360-1450° C. for 15-20 minutes to obtain a melt, ensuring that the Fe block is completely melted.

[0025] Preferably, in step 2), the temperature of the billet homogenization treatment is 750-830° C., the treatment time is 40-60 min, the single-pass processing amount of the fine forging treatment is 10-20%, and the total deformation amount is 60-80%.

[0026] Preferably, in step 4), the processing amount of a single pass of the fine forging treatment is 5-15%, and the total deformation amount is 40-60%; in step 7), the processing amount of a single pass of the fine forging treatment is 5-15%, and the total deformation amount is 50-75%.

[0027] Furthermore, in step 5), the alloy rod is kept at a temperature of 300 to 350° C. for a time of 1 to 2 hours.

[0028] Furthermore, in step 6), the pickling solution used for pickling is a 15% mixed aqueous solution of nitric acid and hydrochloric acid, and the pickling time is 3 minutes.

[0029] Furthermore, in step 3), the peeling thickness is 1.5 mm.

[0030] Compared with the prior art, the advantages of the present invention are: trace Mg elements play a role in further deoxidation, avoiding the reduction of mechanical and electrical properties due to excessive oxygen content of the alloy material; trace Nb, as the core of heterogeneous nucleation, is conducive to grain refinement, and low content of Nb basically does not affect the conductivity of the alloy; trace WC particles can further strengthen the matrix and improve the alloy's resistance to high temperature softening. In addition, the spray deposition process is used to solve the problem of Fe and WC segregation. Compared with mechanical alloying method, gas atomization method, deformation in-situ composite method, external field electromagnetic stirring melting method and other methods, its process is simple, production efficiency is high, and it is easy to apply to industrial production. In addition, in the present invention, the operation design of mixing a trace amount of nano WC powder and nano Cu powder in a mass ratio of 1: (4 to 8) and pressing them into a block, combined with the spray deposition process, can further solve the problem of element segregation. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below with reference to the embodiments.

[0032] Embodiment 1:

[0033] The preparation steps of the high-strength and high-thermal stability copper-iron alloy material of this embodiment are as follows:

[0034] (1) Induction melting: Nano Cu powder and nano WC powder were prepared in a mass ratio of 4:1 and mixed evenly, and then the blank was pressed into a WC-Cu block by a cold isostatic press; the prepared raw materials: high-purity copper, pure Fe block, and pure Nb block were placed in an induction furnace for induction melting. N2 was used for atmosphere protection during the induction melting process. After the raw materials were completely melted, they were kept at 1360°C for 20 minutes to obtain a melt to ensure that the Fe block was completely melted. Then, trace amounts of Mg and WC-Cu blocks were added to the melt and kept at 1310°C for 3 minutes to obtain a melt. Subsequently, the induction melting power was reduced to 20KW for spray deposition molding. The spray deposition atomization pressure was 0.9MPa, the scanning frequency was 25Hz, and the deposition disk rotation frequency was 3.2Hz. The melt was deposited into a billet with a diameter of 80mm and a height of 400mm. The ingot is composed of the following components by weight percentage: Fe: 9%, Nb: 0.05%, WC: 0.1%, Mg: 0.02%, and the balance is Cu and unavoidable impurities;

[0035] (2) hot forging treatment: placing the billet obtained in step (1) in a holding furnace for homogenization treatment at 750° C. for 40 min, then taking out the billet for multi-pass fine forging treatment, with a single-pass processing amount of 10% and a total deformation amount of 60%;

[0036] (3) Peeling treatment: The alloy rod obtained after the multi-pass fine forging treatment in step (2) is subjected to surface peeling treatment, and the peeling thickness is 1.5 mm;

[0037] (4) Cold forging: The alloy rod obtained after the peeling treatment in step (3) is subjected to multiple passes of fine forging at room temperature, with a single pass processing amount of 5% and a total deformation amount of 40%;

[0038] (5) Annealing: The alloy rod obtained after the cold forging treatment in step (4) is subjected to furnace annealing treatment at a heating rate of 5°C / min, and when the temperature rises to 300°C, it is kept at this temperature for 1 hour;

[0039] (6) Pickling treatment: The alloy rod obtained after the annealing treatment in step (5) is pickled, the pickling solution is a 15% nitric acid and hydrochloric acid mixed aqueous solution, and the pickling time is 3 minutes;

[0040] (7) Cold forging treatment: The alloy rod obtained after the pickling treatment in step (6) is subjected to multiple passes of fine forging treatment at room temperature, with a single pass processing amount of 5% and a total deformation amount of 50%, to finally obtain a copper alloy rod.

[0041] The copper alloy rod obtained in this embodiment has a tensile strength of 642 MPa, a conductivity of 68.6% IACS, an elongation after fracture of 8.5%, a softening temperature of 600° C., and an electromagnetic shielding effectiveness of 87 dB when the test frequency range is 30 MHz-10 GHz.

[0042] Embodiment 2:

[0043] The preparation method of the high-performance copper-iron alloy material of this embodiment comprises the following steps in sequence:

[0044] (1) Induction melting: Nano Cu powder and nano WC powder were prepared in a mass ratio of 4:1 and mixed evenly, and then the blank was pressed into a WC-Cu block by a cold isostatic press; the prepared raw materials: high-purity copper, pure Fe block, and pure Nb block were placed in an induction furnace for induction melting. N2 was used for atmosphere protection during the induction melting process. After the raw materials were completely melted, they were kept at 1450°C for 20 minutes to obtain a melt to ensure that the Fe block was completely melted. Then, trace amounts of Mg and WC-Cu blocks were added to the melt and kept at 1420°C for 5 minutes to obtain a melt. Subsequently, the induction melting power was reduced to 20KW for spray deposition molding. The spray deposition atomization pressure was 0.9MPa, the scanning frequency was 25Hz, and the deposition disk rotation frequency was 3.2Hz. The melt was deposited into a billet with a diameter of 80mm and a height of 400mm. The ingot is composed of the following components by weight percentage: Fe: 17%, Nb: 0.1%, WC: 0.2%, Mg: 0.04%, and the balance is Cu and unavoidable impurities;

[0045] (2) hot forging treatment: placing the billet obtained in step (1) in a holding furnace for homogenization treatment at 830° C. for 60 min, then taking out the billet for multi-pass fine forging treatment, with a single-pass processing amount of 20% and a total deformation amount of 80%;

[0046] (3) Peeling treatment: The alloy rod obtained after the multi-pass fine forging treatment in step (2) is subjected to surface peeling treatment, and the peeling thickness is 1.5 mm;

[0047] (4) Cold forging: The alloy rod obtained after the peeling treatment in step (3) is subjected to multiple passes of fine forging at room temperature, with a single pass processing amount of 15% and a total deformation amount of 60%;

[0048] (5) Annealing: The alloy rod obtained after the cold forging treatment in step (4) is subjected to furnace annealing treatment at a heating rate of 5°C / min, and when the temperature rises to 350°C, it is kept at this temperature for 2h;

[0049] (6) Pickling treatment: The alloy rod obtained after the annealing treatment in step (5) is pickled, and the pickling solution is a 15% nitric acid and hydrochloric acid mixed aqueous solution, and the pickling time is 3 minutes;

[0050] (7) Cold forging treatment: The alloy rod obtained after the pickling treatment in step (6) is subjected to multiple passes of fine forging treatment at room temperature, with a single pass processing amount of 15% and a total deformation amount of 75%, to finally obtain a copper alloy rod.

[0051] The copper alloy rod obtained in this embodiment has a tensile strength of 837 MPa, a conductivity of 52.3% IACS, an elongation after fracture of 4%, a softening temperature of 620° C., and an electromagnetic shielding effectiveness of 94 dB in a test frequency range of 30 MHz-10 GHz.

[0052] Embodiment 3:

[0053] The preparation method of the high-performance copper-iron alloy material of this embodiment comprises the following steps in sequence:

[0054] (1) Induction melting: Nano Cu powder and nano WC powder were prepared in a mass ratio of 4:1 and mixed evenly, and then the blank was pressed into a WC-Cu block by a cold isostatic press; the prepared raw materials: high-purity copper, pure Fe block, and pure Nb block were placed in an induction furnace for induction melting. N2 was used for atmosphere protection during the induction melting process. After the raw materials were completely melted, they were kept at 1400°C for 18 minutes to obtain a melt to ensure that the Fe block was completely melted. Then, trace Mg and WC-Cu blocks were added to the melt and kept at 1380°C for 4 minutes to obtain a melt. Subsequently, the induction melting power was reduced to 20KW for spray deposition molding. The spray deposition atomization pressure was 0.9MPa, the scanning frequency was 25Hz, and the deposition disk rotation frequency was 3.2Hz. The melt was deposited into an ingot with a diameter of 80mm and a height of 400mm. The ingot is composed of the following components by weight percentage: Fe: 13%, Nb: 0.07%, WC: 0.15%, Mg: 0.03%, and the balance is Cu and unavoidable impurities;

[0055] (2) hot forging treatment: placing the billet obtained in step (1) in a holding furnace for homogenization treatment at 800° C. for 50 min, then taking out the billet for multi-pass fine forging treatment, with a single-pass processing amount of 10% and a total deformation amount of 70%;

[0056] (3) Peeling treatment: The alloy rod obtained after the multi-pass fine forging treatment in step (2) is subjected to surface peeling treatment, and the peeling thickness is 1.5 mm;

[0057] (4) Cold forging: The alloy rod obtained after the peeling treatment in step (3) is subjected to multiple passes of fine forging at room temperature, with a single pass processing amount of 10% and a total deformation amount of 50%;

[0058] (5) Annealing: The alloy rod obtained after the cold forging treatment in step (4) is subjected to furnace annealing treatment at a heating rate of 5°C / min, and when the temperature rises to 320°C, it is kept at this temperature for 1.5 hours;

[0059] (6) Pickling treatment: The alloy rod obtained after the annealing treatment in step (5) is pickled, and the pickling solution is a 15% nitric acid and hydrochloric acid mixed aqueous solution, and the pickling time is 3 minutes;

[0060] (7) Cold forging treatment: The alloy rod obtained after the pickling treatment in step (6) is subjected to multiple passes of fine forging treatment at room temperature, with a single pass processing amount of 10% and a total deformation amount of 70%, to finally obtain a copper alloy rod.

[0061] The copper alloy rod obtained in this embodiment has a tensile strength of 749 MPa, a conductivity of 59.4% IACS, an elongation after fracture of 5.5%, a softening temperature of 610° C., and an electromagnetic shielding effectiveness of 91 dB when the test frequency range is 30 MHz-10 GHz.

[0062] Embodiment 4:

[0063] The preparation method of the high-performance copper-iron alloy material of this embodiment comprises the following steps in sequence:

[0064] (1) Induction melting: Nano Cu powder and nano WC powder were prepared in a mass ratio of 4:1 and mixed evenly, and then the blank was pressed into a WC-Cu block by a cold isostatic press; the prepared raw materials: high-purity copper, pure Fe block, and pure Nb block were placed in an induction furnace for induction melting. N2 was used for atmosphere protection during the induction melting process. After the raw materials were completely melted, they were kept at 1400°C for 18 minutes to obtain a melt to ensure that the Fe block was completely melted. Then, trace amounts of Mg and WC-Cu blocks were added to the melt and kept at 1380°C for 5 minutes to obtain a melt. Subsequently, the induction melting power was reduced to 20KW for spray deposition molding. The spray deposition atomization pressure was 0.9MPa, the scanning frequency was 25Hz, and the deposition disk rotation frequency was 3.2Hz. The melt was deposited into a billet with a diameter of 80mm and a height of 400mm. The ingot is composed of the following components by weight percentage: Fe: 12%, Nb: 0.05%, WC: 0.2%, Mg: 0.02%, and the balance is Cu and unavoidable impurities;

[0065] (2) hot forging treatment: placing the billet obtained in step (1) in a holding furnace for homogenization treatment at 800° C. for 50 min, then taking out the billet for multi-pass fine forging treatment, with a single-pass processing amount of 20% and a total deformation amount of 60%;

[0066] (3) Peeling treatment: The alloy rod obtained after the multi-pass fine forging treatment in step (2) is subjected to surface peeling treatment, and the peeling thickness is 1.5 mm;

[0067] (4) Cold forging: The alloy rod obtained after the peeling treatment in step (3) is subjected to multiple passes of fine forging at room temperature, with a single pass processing amount of 15% and a total deformation amount of 60%;

[0068] (5) Annealing: The alloy rod obtained after the cold forging treatment in step (4) is subjected to furnace annealing treatment at a heating rate of 5°C / min, and when the temperature rises to 320°C, it is kept at this temperature for 1.5 hours;

[0069] (6) Pickling treatment: The alloy rod obtained after the annealing treatment in step (5) is pickled, and the pickling solution is a 15% nitric acid and hydrochloric acid mixed aqueous solution, and the pickling time is 3 minutes;

[0070] (7) Cold forging treatment: The alloy rod obtained after the pickling treatment in step (6) is subjected to multiple passes of fine forging treatment at room temperature, with a single pass processing amount of 5% and a total deformation amount of 60%, to finally obtain a copper alloy rod.

[0071] The copper alloy rod obtained in this embodiment has a tensile strength of 706 MPa, a conductivity of 681.3% IACS, an elongation after fracture of 6%, a softening temperature of 620° C., and an electromagnetic shielding effectiveness of 90 dB when the test frequency range is 30 MHz-10 GHz.

[0072] Embodiment 5:

[0073] The preparation method of the high-performance copper-iron alloy material of this embodiment comprises the following steps in sequence:

[0074] (1) Induction melting: Nano Cu powder and nano WC powder were prepared in a mass ratio of 4:1 and mixed evenly, and then the blank was pressed into a WC-Cu block by a cold isostatic press; the prepared raw materials: high-purity copper, pure Fe block, and pure Nb block were placed in an induction furnace for induction melting. N2 was used for atmosphere protection during the induction melting process. After the raw materials were completely melted, they were kept at 1450°C for 20 minutes to obtain a melt to ensure that the Fe block was completely melted. Then, trace amounts of Mg and WC-Cu blocks were added to the melt and kept at 1420°C for 5 minutes to obtain a melt. Subsequently, the induction melting power was reduced to 20KW for spray deposition molding. The spray deposition atomization pressure was 0.9MPa, the scanning frequency was 25Hz, and the deposition disk rotation frequency was 3.2Hz. The melt was deposited into a billet with a diameter of 80mm and a height of 400mm. The ingot is composed of the following components by weight percentage: Fe: 15%, Nb: 0.1%, WC: 0.1%, Mg: 0.03%, and the balance is Cu and unavoidable impurities;

[0075] (2) hot forging treatment: placing the billet obtained in step (1) in a holding furnace for homogenization treatment at 800° C. for 60 min, then taking out the billet for multi-pass fine forging treatment, with a single-pass processing amount of 10% and a total deformation amount of 70%;

[0076] (3) Peeling treatment: The alloy rod obtained after the multi-pass fine forging treatment in step (2) is subjected to surface peeling treatment, and the peeling thickness is 1.5 mm;

[0077] (4) Cold forging: The alloy rod obtained after the peeling treatment in step (3) is subjected to multiple passes of fine forging at room temperature, with a single pass processing amount of 10% and a total deformation amount of 50%;

[0078] (5) Annealing: The alloy rod obtained after the cold forging treatment in step (4) is subjected to furnace annealing treatment at a heating rate of 5°C / min, and when the temperature rises to 350°C, it is kept at this temperature for 2h;

[0079] (6) Pickling treatment: The alloy rod obtained after the annealing treatment in step (5) is pickled, the pickling solution is a 15% nitric acid and hydrochloric acid mixed aqueous solution, and the pickling time is 3 minutes;

[0080] (7) Cold forging treatment: The alloy rod obtained after the pickling treatment in step (6) is subjected to multiple passes of fine forging treatment at room temperature, with a single pass processing amount of 15% and a total deformation amount of 60%, to finally obtain a copper alloy rod.

[0081] The copper alloy rod obtained in this embodiment has a tensile strength of 774 MPa, a conductivity of 57.7% IACS, an elongation after fracture of 5%, a softening temperature of 610° C., and an electromagnetic shielding effectiveness of 92 dB in a test frequency range of 30 MHz-10 GHz.

[0082] Embodiment 6:

[0083] This embodiment is basically the same as the embodiment 1, except that in step (1) of this embodiment, the nano Cu powder and the nano WC powder are mixed in a mass ratio of 8:1 and then the blank is pressed into a block by a cold isostatic press. At the same time, the spray deposition process of this embodiment is: the atomization pressure is 1.1 MPa, the scanning frequency is 28 Hz, the deposition disk rotation frequency is 3.5 Hz, and the melt is deposited into a billet with a diameter of 78 mm and a height of 420 mm.

[0084] Embodiment 7:

[0085] This embodiment is basically the same as the embodiment 1, except that in step (1) of this embodiment, the nano Cu powder and the nano WC powder are mixed in a mass ratio of 6:1 and then the blank is pressed into a block by a cold isostatic press. At the same time, the spray deposition process of this embodiment is: the atomization pressure is 1.0 MPa, the scanning frequency is 23 Hz, the deposition disk rotation frequency is 3.0 Hz, and the melt is deposited into a billet with a diameter of 85 mm and a height of 390 mm.

[0086] The above specific examples are further detailed descriptions of the present invention, and it cannot be determined that the specific implementation methods of the present invention are limited to these. Without departing from the alloy composition range and deformation heat treatment process proposed by the present invention, appropriate composition adjustments and improvements can be made, but they should all be deemed to fall within the scope of protection of the claims submitted by the present invention.

Claims

1. A copper-iron alloy material, characterized in that: The alloy is composed of the following components in weight percentage: Fe: 9-17%, Nb: 0.05-0.1%, WC: 0.1-0.2%, Mg: 0.02-0.04%, and the remainder is Cu and inevitable impurities.

2. The copper-iron alloy material according to claim 1, characterized in that: The copper-iron alloy material has a tensile strength of 642-837 MPa, a conductivity of 52.3-68.6% IACS, an elongation after fracture of 4%-8.5%, a softening temperature of ≥600°C, and an electromagnetic shielding effect of ≥87 dB.

3. A method for preparing the copper-iron alloy material as claimed in claim 1 or 2, characterized in that Here are the steps: 1) Induction melting: Nano Cu powder and nano WC powder are prepared in a mass ratio of (4-8):1 and mixed evenly, and then pressed into WC-Cu blocks by a cold isostatic press; the prepared raw materials: high-purity copper, pure Fe blocks, and pure Nb blocks are placed in an induction furnace and induction melted under the protection of N2 atmosphere, and a molten liquid is obtained after the raw materials are completely melted, and then a trace amount of Mg and WC-Cu blocks are added to the molten liquid and kept at a temperature of 1310-1420°C for 3-5 minutes, and then the induction melting power is reduced to 18-20KW for spray deposition molding to obtain an ingot; 2) hot forging treatment: placing the billet obtained in step 1) in a holding furnace for homogenization treatment, then taking out the billet for multiple passes of fine forging treatment to obtain an alloy rod; 3) Peeling treatment: The alloy rod obtained in step 2) is subjected to surface deoxidation treatment; 4) Cold forging treatment: the peeled alloy rod in step 3) is subjected to multiple passes of fine forging treatment at room temperature; 5) Annealing: annealing the alloy rod after the cold forging treatment in step 4); 6) Pickling treatment: Pickling the alloy rod after annealing in step 5) to remove the oxide scale on the surface of the alloy rod after annealing; 7) Cold forging treatment: The alloy rod after the pickling treatment in step (6) is subjected to multiple passes of fine forging treatment at room temperature to obtain a copper-iron alloy material.

4. The preparation method according to claim 3, characterized in that: The process of spray deposition in step 1) is: the atomization pressure is 0.9-1.1 MPa, the scanning frequency is 23-28 Hz, the rotation frequency of the deposition disk is 3.0-3.5 Hz, and the melt is deposited into an ingot with a diameter of 78-85 mm and a height of 390-420 mm.

5. The preparation method according to claim 3, characterized in that: In step 1), after the raw materials are completely melted, the temperature is kept at 1360-1450° C. for 15-20 minutes to obtain a melt.

6. The preparation method according to claim 3, characterized in that: In step 2), the temperature of the billet homogenization treatment is 750-830° C., the treatment time is 40-60 min, the single-pass processing amount of the fine forging treatment is 10-20%, and the total deformation amount is 60-80%.

7. The preparation method according to claim 3, characterized in that: In step 4), the processing amount of a single pass of the fine forging treatment is 5-15%, and the total deformation amount is 40-60%; in step 7), the processing amount of a single pass of the fine forging treatment is 5-15%, and the total deformation amount is 50-75%.

8. The preparation method according to claim 3, characterized in that: In step 5), the alloy rod is kept at a temperature of 300 to 350° C. for 1 to 2 hours.

9. The preparation method according to claim 3, characterized in that: In step 6), the pickling solution used for pickling is a 15% mixed aqueous solution of nitric acid and hydrochloric acid, and the pickling time is 3 minutes.

10. The preparation method according to claim 3, characterized in that: In step 3), the peeling thickness is 1.5 mm.

Citation Information

Patent Citations

  • A preparation method of Cu-Fe composite material

    CN104232962B

  • Micro-alloying method capable of improving comprehensive mechanical property of Cu-Fe alloy

    CN111334683A

  • High-conductivity high-strength copper-iron alloy and preparation method thereof

    CN111424188A

  • A high-conductivity, high-strength copper-iron alloy and its preparation method

    CN111424188B

  • High-conductivity high-strength copper-iron-calcium alloy and preparation method thereof

    CN111593227A